From Sunshine to Wellness: Understanding Vitamin D Impact on Menstrual Health - Dhanyaa Muthukumaran; Jawaher Abdullah Bin Jumah; Rajeshkumar Shanmugam; Chinnaperumal Kamaraj (Advances in Public Health)
Conclusion: This review highlights the pivotal role of vitamin D in women’s reproductive health, highlighting its comprehensive involvement in the menstrual cycle and its potential to enhance overall well-being. The findings suggest that ensuring adequate vitamin D levels, whether through sunlight exposure, diet, or supplementation, may offer significant benefits for menstrual health and related aspects of women’s health.